Stress Testing of Financial Systems : An Overview of Issues, Methodologies, and FSAP Experiences - Martinez Peria, Maria (IMF Working Papers; Working Paper, 2001)
The paper has three objectives. After a general introduction to some of the concepts and basic techniques of stress testing, the paper gives an overview of some of the conceptual issues involved in evaluating risks at the aggregated level of financial systems. Second, this study provides a basic framework and toolkit for conducting stress tests. Finally, the paper reviews some of the stress-testing analyses conducted in the context of the Financial Sector Assessment Program (FSAP) and suggests simplified approaches to deal with situations where the quantity and quality of the data is less than ideal.